Silicon-carbon negative electrode material and preparation method thereof
By controlling the content of high-priced silicon in the silicon-carbon anode material and increasing the content of low-priced silicon, the problem of high volume expansion rate of silicon-based anode material and the oxidation of silicon into high-priced silicon is solved, and the performance of secondary battery with high deliquency capacity and first-time Coulomb efficiency is achieved.
Patent Information
- Application Number
- CN202311619241.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-28
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-11-28
AI Technical Summary
The volume expansion rate of silicon-based anode material increases after being embedded with lithium, which may lead to cracking of the negative electrode sheet. At the same time, the silicon in the silicon-carbon anode material is oxidized to high-valent silicon, resulting in a decrease in the capacity of grams and a decrease in the first Coulomb efficiency.
By controlling the content of high-valent silicon in the silicon-carbon anode material, it is less than 25% in the area from the surface to a depth of 10 nm, to increase the content of low-valent silicon, thereby improving the deliquency capacity of the anode material and the first-time Coulomb efficiency.
It effectively improves the discharge capacity and first-time Coulomb efficiency of the secondary battery, reduces lithium loss, and extends the service life of the battery.
Smart Images

Figure CN119852338A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a silicon-carbon negative electrode material and a preparation method thereof. Background Art
[0002] As the power of electrical devices such as mobile phones, computers, power tools, and electric vehicles continues to increase, people's requirements for the energy density of secondary batteries are also increasing. Silicon-based negative electrode materials have a high gram capacity. At present, the industry has begun to increase the energy density of secondary batteries by adding silicon-based negative electrode materials to the negative electrode sheets. However, the volume expansion rate of silicon-based negative electrode materials increases after lithium is inserted, which may cause cracks in the negative electrode sheets.
[0003] In order to solve the problem of high volume expansion rate of silicon-based negative electrode materials, silicon-carbon negative electrode materials formed by depositing silicon inside porous carbon are currently mostly used, and the voids inside the porous carbon are used to weaken the expansion of silicon-based materials. However, because the silicon in the silicon-carbon negative electrode material is oxidized into high-valent silicon, the gram capacity of the silicon-carbon negative electrode material is reduced, which affects the first coulomb efficiency of the secondary battery. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a silicon-carbon negative electrode material and a preparation method, the silicon-carbon negative electrode material has high lithium removal gram capacity and first coulomb efficiency, thereby being able to improve the discharge gram capacity and first coulomb efficiency of the secondary battery.
[0005] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a silicon-carbon negative electrode material, which includes a carbon skeleton with a pore structure and a silicon-based material arranged in the pore structure, and in an area formed from the surface of the silicon-carbon negative electrode material to an area extending 10 nm inward from the surface, relative to the total amount of low-valent silicon and high-valent silicon, the content of the high-valent silicon is less than 25%, wherein the low-valent silicon is silicon with a valence of 0 to 2, and the high-valent silicon is silicon with a valence of 3 to 4.
[0006] The silicon-carbon negative electrode material of the present application suppresses the content of high-valent silicon to a low level, making the content of low-valent silicon high, thereby improving the lithium removal gram capacity and first coulomb efficiency of the negative electrode material, and effectively improving the discharge gram capacity and first coulomb efficiency of the secondary battery.
[0007] In some embodiments, in the region from the surface of the silicon-carbon negative electrode material to the region extending 10 nm inward from the surface, the content of the high-valent silicon is less than or equal to 20% relative to the total amount of low-valent silicon and high-valent silicon. Thus, the negative electrode material has a higher lithium removal gram capacity and first coulomb efficiency, and the resulting secondary battery has a better discharge gram capacity and first coulomb efficiency.
[0008] In some embodiments, in the region from 10 nm to 20 nm from the surface of the silicon-carbon negative electrode material, the content of the high-price silicon is less than or equal to 20% relative to the total amount of low-price silicon and high-price silicon, and optionally, less than or equal to 10%. Thus, the content of high-price silicon in the silicon-carbon negative electrode material of the present application is further suppressed at a low level, which is more conducive to improving the lithium removal gram capacity and the first coulombic efficiency of the negative electrode material.
[0009] In some embodiments, in the region from 20 nm to 30 nm from the surface of the silicon-carbon negative electrode material, the content of the high-price silicon is less than or equal to 10% relative to the total amount of low-price silicon and high-price silicon, and optionally, less than or equal to 5%. Thus, the content of high-price silicon in the silicon-carbon negative electrode material of the present application is further suppressed at a low level, which is more conducive to improving the lithium removal gram capacity and the first coulombic efficiency of the negative electrode material.
[0010] In some embodiments, the silicon-carbon negative electrode material satisfies at least one of the following conditions: (1) the volume distribution particle size Dv50 of the silicon-carbon negative electrode material is 5 μm-10 μm, and can be 6 μm-9 μm; (2) the specific surface area of the silicon-carbon negative electrode material is less than or equal to 5 m 2 / g, can be selected to be less than or equal to 2m 2 / g; (3) The powder compaction density of the silicon-carbon negative electrode material under a pressure of 3000N is 0.8g / cm 3 -1.2g / cm 3 , optional 0.9g / cm 3 -1.2g / cm 3 ; (4) The tap density of the silicon-carbon negative electrode material is 0.9 g / cm 3 -1.1g / cm 3 , optional 1.0g / cm 3 -1.1g / cm 3 (5) The lithium-free gram capacity of the silicon-carbon negative electrode material is 800mAh / g-2500mAh / g, and can be optionally 1000mAh / g-2000mAh / g. By making the particle size, compaction density and tap density of the silicon-carbon negative electrode material within the above range, the compaction density of the electrode sheet can be effectively increased, and the energy density of the battery cell can be increased. In addition, by making the specific surface area within 5m 2 / g or less, which can reduce the contact area between the particles and the electrolyte as much as possible and improve the initial coulombic efficiency, cycle and storage performance.
[0011] In some embodiments, the pore volume of the carbon skeleton is 0.4 cm 3 / g-1.5cm 3 / g, optional 0.6cm 3 / g-1.2cm 3 / g; and / or, relative to the pore volume, the volume proportion of micropores with a pore diameter less than 2nm is greater than or equal to 60%, and can be greater than or equal to 80%. Thus, the silicon-based material is mainly deposited in the micropores, and the higher the proportion of micropores, the more silicon-based material is deposited, and the higher the corresponding lithium removal capacity.
[0012] In some embodiments, the surface of the silicon-carbon negative electrode material has a coating layer; optionally, the coating layer is a carbon coating layer. The present application greatly reduces the risk of silicon in the negative electrode material being oxidized to form high-valent silicon through the coating layer, and reduces the content of high-valent silicon in the silicon-carbon negative electrode material.
[0013] The second aspect of the present application provides a method for preparing the silicon-carbon negative electrode material of the first aspect, comprising the following steps:
[0014] a silicon-carbon particle forming step of reacting a carbon skeleton having a pore structure with a silicon source gas to form silicon-carbon particles having a silicon-based material in the pore structure; and
[0015] The silicon-carbon particle processing step is to introduce a mixed gas including a carbon source gas and an inert gas into the silicon-carbon particles at a ventilation volume greater than 0 L / min and less than or equal to 10 L / min under the conditions of a temperature of 500°C-800°C and a pressure of 0 kpa-1 kpa, wherein the carbon source gas is selected from at least one of ethane, ethylene, acetylene, and methane.
[0016] Through the above preparation method, a uniform and dense coating layer can be formed on the surface of the silicon-carbon particles, which greatly reduces the risk of silicon in the negative electrode material being oxidized to form high-valent silicon, and can obtain a silicon-carbon negative electrode material with high lithium removal gram capacity and first coulomb efficiency.
[0017] In some embodiments, in the silicon-carbon particle treatment step, the mixed gas is introduced into the silicon-carbon particles at a temperature of 550° C. to 650° C. and a pressure of 0 kPa to 0.5 kPa at a flow rate of 0.5 L / min to 4 L / min. Thus, a more uniform and dense coating layer can be formed, which is conducive to obtaining a silicon-carbon negative electrode material with higher lithium removal gram capacity and first coulomb efficiency.
[0018] In some embodiments, the mixed gas includes 10% to 70% by volume of acetylene, 0% to 20% by volume of methane, and 10% to 90% by volume of inert gas, and optionally, includes 15% to 60% by volume of acetylene, 5% to 10% by volume of methane, and 30% to 80% by volume of inert gas. Thus, by using a specific mixed gas, the decomposition rate can be controlled, so that carbon is slowly coated on the particle surface, making the coating layer denser.
[0019] In some embodiments, the step of forming silicon-carbon particles includes the following steps: evacuating the reaction device and then introducing an inert gas, thereby removing oxygen from the reaction device and greatly reducing the risk of silicon deposited in the negative electrode material being oxidized by oxygen in the reaction device to form high-valent silicon.
[0020] In some embodiments, the step of forming silicon-carbon particles includes the following steps: in a reaction device, heating the carbon skeleton having a porous structure to 400° C.-550° C. to remove oxygen from the carbon skeleton. Thus, the oxygen adsorbed by the carbon skeleton itself can be removed, and the risk of silicon deposited in the negative electrode material being oxidized by the oxygen adsorbed by the carbon skeleton itself to form high-valent silicon can be greatly reduced.
[0021] In some embodiments, the step of forming silicon-carbon particles includes the following steps: introducing a mixed gas of silicon source gas and inert gas into a reaction device, and depositing at a temperature of 400° C. to 550° C. for 2 to 10 hours to form silicon-carbon particles. In this way, silicon can be uniformly deposited inside the porous carbon.
[0022] In some embodiments, the silicon source gas is selected from one or more of monosilane, disilane, dichlorosilane, and trichlorosilane. Optionally, the silicon source gas is monosilane.
[0023] In some embodiments, the inert gas is argon, thereby making the silicon source gas non-flammable and preventing silicon from being oxidized.
[0024] The third aspect of the present application also provides a negative electrode plate, comprising the silicon-carbon negative electrode material of the first aspect of the present application or the silicon-carbon negative electrode material prepared by the second aspect.
[0025] The fourth aspect of the present application also provides a secondary battery, comprising the negative electrode sheet of the third aspect of the present application. The secondary battery has excellent first coulombic efficiency.
[0026] The fifth aspect of the present application further provides an electrical device, comprising the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0028] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0029] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0030] Figure 4It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0031] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0032] Figure 6 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0033] Figure 7 This is an XPS graph analyzing the region from the surface to the region extending 10 nm inward from the surface of the silicon-carbon negative electrode material of Example 1 of the present application.
[0034] Figure 8 This is an XPS graph analyzing the region from the surface to the region extending 10 nm from the surface to the inside of the silicon-carbon negative electrode material of Comparative Example 1 of the present application.
[0035] Description of reference numerals:
[0036] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0037] Hereinafter, the embodiments of the silicon-carbon negative electrode material and the preparation method thereof of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0038] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0039] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0040] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0041] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0042] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0043] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0044] With the extensive research on silicon-carbon negative electrode materials, people have put forward higher requirements on the performance of silicon-carbon negative electrode materials. The inventors found that increasing the content of low-valent silicon in silicon-carbon negative electrode materials helps to improve the lithium-free gram capacity of silicon-carbon negative electrode materials. However, in the current silicon-carbon negative electrode materials, low-valent silicon is inevitably oxidized to form high-valent silicon, resulting in a decrease in the lithium-free gram capacity and the first coulomb efficiency of the silicon-carbon negative electrode materials. Moreover, these high-valent silicons easily form irreversible lithium silicates with lithium ions, which reduces the amount of active lithium embedded and extracted between the positive and negative electrode sheets, causing lithium loss, resulting in a decrease in the discharge gram capacity and the first coulomb efficiency of the secondary battery.
[0045] In view of this, the present application proposes a silicon-carbon negative electrode material, which includes a carbon skeleton with a pore structure and a silicon-based material arranged in the pore structure. In the area from the surface of the above-mentioned silicon-carbon negative electrode material to the area extending 10nm from the surface to the inside, relative to the total amount of low-valent silicon and high-valent silicon, the content of the high-valent silicon is less than 25%, the low-valent silicon is 0-valent to 2-valent silicon, and the high-valent silicon is 3-valent to 4-valent silicon.
[0046] The content of high-valent silicon in the silicon-carbon negative electrode material of the present application is suppressed to a low level, so that the content of low-valent silicon is greater than or equal to 75%, thereby improving the lithium removal gram capacity and the first coulombic efficiency of the negative electrode material. Moreover, the low content of high-valent silicon reduces the formation of lithium silicates and significantly reduces lithium loss, thereby effectively improving the discharge gram capacity and the first coulombic efficiency of the secondary battery.
[0047] In the present application, the above-mentioned high-valent silicon and low-valent silicon can be quantified by XPS. In the XPS graph, the binding energy of low-valent silicon is 98-102eV, corresponding to valence states of 0, 1 and 2, and the area (S1) enclosed by the curve and the baseline is the atomic molar amount of low-valent silicon. The binding energy of high-valent silicon is 102eV-106eV, corresponding to valence states of 3 and 4, and the area (S2) enclosed by the curve and the baseline is the atomic molar amount of high-valent silicon. Relative to the total amount of low-valent silicon and high-valent silicon, the content of high-valent silicon = S2 / (S1+S2)×100%, and the content of low-valent silicon = S1 / (S1+S2)×100%. The baseline is the line connecting two points on the test curve, and the two points are X=98eV and X=106eV respectively.
[0048] In some embodiments, in the region extending from the surface of the silicon-carbon negative electrode material to the inner region extending 10 nm from the surface, the content of high-valent silicon (denoted as C 10) is: 24%, 23%, 22%, 21%, 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, etc. or a value between any two values, but not limited thereto. In some embodiments, in the area from the surface of the silicon-carbon negative electrode material to the area extending 10 nm from the surface to the inside, it is preferred that C 10 Less than or equal to 20%, preferably C 10 Less than or equal to 10%. The smaller the content of high-valent silicon in the area extending 10nm from the surface of the silicon-carbon negative electrode material to the inside, the higher the content of low-valent silicon, the higher the lithium removal capacity of the silicon-carbon negative electrode material, and the lower the content of high-valent silicon, the less the formation of lithium silicate, which greatly improves the discharge capacity and first coulomb efficiency of the secondary battery.
[0049] In some embodiments, the content of high-valent silicon (denoted as C 20 ) is less than or equal to 20%. For example, the content of high-valent silicon is: 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, etc. or a value between any two values, but not limited to this. In some embodiments, in the area from 10nm away from the surface of the silicon-carbon negative electrode material to 20nm away from the surface of the silicon-carbon negative electrode material, preferably C 20 Less than 10%.
[0050] In some embodiments, in the region from 20 nm to 30 nm from the surface of the silicon-carbon negative electrode material, the content of high-valent silicon (denoted as C 30 ) is less than or equal to 10%. For example, the content of high-price silicon (C 30 ) can be 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, etc. or a value between any two values, but is not limited thereto. Preferably, in the region from 20 nm to 30 nm from the surface of the silicon-carbon negative electrode material, C 30 Less than or equal to 5%.
[0051] Regarding the above C 10 , C 20 , C 30 For the specific determination method, see the description in the examples section.
[0052] In some embodiments, the silicon-carbon negative electrode material satisfies at least one of the following conditions: (1) the volume distribution particle size Dv50 of the silicon-carbon negative electrode material is 5 μm-10 μm, for example, it can be 5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, preferably 6 μm-9 μm; (2) the specific surface area of the silicon-carbon negative electrode material is less than or equal to 5 m 2 / g, for example, 5m 2 / g, 4m 2 / g, 3m 2 / g, 2m 2 / g, 1.5m 2 / g, 1m 2 / g, etc., preferably less than or equal to 2m 2 / g; (3) The powder compaction density of the silicon-carbon negative electrode material under a pressure of 3000N is 0.8g / cm 3 -1.2g / cm 3 , for example, it can be 0.8 g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , preferably 0.9 g / cm 3 -1.2g / cm 3 ; (4) The tap density of the silicon-carbon negative electrode material is 0.9 g / cm 3 -1.1g / cm 3 , for example, it can be 0.9 g / cm 3 , 0.95g / cm 3 , 1.0g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , preferably 1.0 g / cm 3 -1.1g / cm 3(5) The lithium-free gram capacity of the silicon-carbon negative electrode material is 800mAh / g-2500mAh / g, for example, it can be 800mAh / g, 900mAh / g, 1000mAh / g, 1100mAh / g, 1200mAh / g, 1300mAh / g, 1400mAh / g, 1500mAh / g, 1600mAh / g, 1700mAh / g, 1800mAh / g, 1900mAh / g, 2000mAh / g, 2100mAh / g, etc., preferably 1000mAh / g-2000mAh / g. By making the particle size, compaction density and tap density of the silicon-carbon negative electrode material within the above range, the compaction density of the pole piece can be effectively increased, and the energy density of the battery cell can be increased. In addition, by making the specific surface area within 5m 2 / g or less, which can minimize the contact area between the particles and the electrolyte and improve the initial coulombic efficiency, cycle and storage performance.
[0053] In this application, the volume distribution particle size Dv50 of the material has a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0054] In this application, the specific surface area of a material has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The test instrument can be the Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA.
[0055] In this application, the powder compaction density of a material has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine (for example, a UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. An exemplary test method is as follows: weigh 1g of sample powder, add it to a mold with a bottom area of 1.327cm2, pressurize to 300kg, maintain pressure for 30s, then release the pressure, maintain for 10s, and then record and calculate the powder compaction density of the material under a pressure of 3000N.
[0056] In this application, the tap density of a material is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured using a powder tap density tester in accordance with GB / T 5162-2006. The test instrument can be Dandong Better BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.
[0057] In the present application, the lithium removal gram capacity of a material has a well-known meaning in the art and can be tested by methods known in the art. For specific testing methods, please refer to the description in the examples.
[0058] In some embodiments, the pore volume of the carbon skeleton is 0.4 cm 3 / g-1.5cm 3 / g, optional 0.6cm 3 / g-1.2cm 3 / g, and / or, relative to the above pore volume, the volume proportion of micropores with a pore diameter less than 2nm is greater than or equal to 60%, optionally greater than or equal to 80%. As a result, the silicon-based material is mainly deposited in the micropores, and the higher the proportion of micropores, the more silicon-based material is deposited, and the corresponding lithium removal gram capacity is higher. In some embodiments, the above silicon-based material can be amorphous hard carbon.
[0059] In some embodiments, the surface of the silicon-carbon negative electrode material has a coating layer; optionally, the coating layer is a carbon coating layer. By providing a uniform and dense coating layer, the present application can further prevent oxygen in the air from entering the negative electrode material, greatly reducing the risk of silicon in the silicon-carbon negative electrode material being oxidized to form high-priced silicon, and reducing the content of high-priced silicon in the silicon-carbon negative electrode material.
[0060] In addition, the present application provides a method for preparing the above-mentioned silicon-carbon negative electrode material, which includes a silicon-carbon particle forming step (step (a)), in which a carbon skeleton having a pore structure reacts with a silicon source gas to form silicon-carbon particles having a silicon-based material in the pore structure; and a silicon-carbon particle processing step (step (b)), in which a mixed gas including a carbon source gas and an inert gas is introduced into the silicon-carbon particles at a flow rate greater than 0 L / min and less than or equal to 10 L / min under the conditions of a temperature of 500°C-700°C and a pressure of 0 kpa-1 kpa, wherein the carbon source gas is selected from at least one of ethane, ethylene, acetylene, and methane.
[0061] Therefore, by adopting a specific temperature, pressure, ventilation volume and mixed gas, the decomposition rate of the carbon source gas can be effectively controlled, which is conducive to forming a uniform and dense coating layer on the surface of the silicon-carbon particles. Therefore, the risk of silicon in the silicon-carbon particles being oxidized by oxygen in the air to form high-valent silicon can be effectively reduced, and the content of high-valent silicon in the particles can be reduced, so that C10 , C 20 and C 30 By selecting the above carbon source gas, the coating can be uniform and complete.
[0062] In some embodiments, in step (b), as temperature, for example, it can be 500°C, 550°C, 600°C, 650°C, 700°C or a value between the ranges of any two of these values. As pressure, for example, it can be 0kpa, 50Pa, 100Pa, 150Pa, 200Pa, 250Pa, 300Pa, 350Pa, 400Pa, 450Pa, 500Pa, 550Pa, 600Pa, 650Pa, 700Pa, 750kPa, 800Pa, 850Pa, 900Pa, 950Pa, 1000Pa (1kpa) or a value between the ranges of any two of these values. By controlling the temperature and pressure within the above range, the decomposition rate of the carbon source gas can be effectively controlled, which is conducive to forming a uniform and dense coating layer.
[0063] In some embodiments, in step (b), the ventilation volume can be, for example, 0.5 L / min, 1.0 L / min, 1.5 L / min, 2.0 L / min, 2.5 L / min, 3.0 L / min, 3.5 L / min, 4.0 L / min, 4.5 L / min, 5.0 L / min, 5.5 L / min, 6.0 L / min, 6.5 L / min, 7.0 L / min, 7.5 L / min, 8.0 L / min, 8.5 L / min, 9.0 L / min, 9.5 L / min, 10.0 L / min or a value between the ranges formed by any two of these values. By controlling the ventilation volume within the above range, the carbon source gas can be fully reacted, the utilization rate of the carbon source gas can be improved, and it is conducive to forming a uniform and dense coating layer.
[0064] In some embodiments, in step (b), preferably, the mixed gas is introduced at a temperature of 550°C-650°C and a pressure of 0kPa-500Pa at a flow rate of 0.5L / min-4L / min. Under the above conditions, a denser coating layer can be formed, which further reduces the possibility of oxygen in the air entering the particles to oxidize silicon, and can further reduce C 10 , C 20 and C 30 .
[0065] In some embodiments, preferably, the mixed gas comprises 10%-70% acetylene, 0%-20% methane and 10%-90% inert gas, and more preferably, the mixed gas comprises 15%-60% acetylene, 5%-10% methane and 30%-80% inert gas. Acetylene has a low decomposition temperature and decomposes rapidly. Adding a certain amount of methane can control the decomposition rate of acetylene, so that carbon is slowly coated on the surface of the particles, so that the coating layer is dense.
[0066] Inert gas is a gas that does not react with silicon material. For example, inert gas includes but is not limited to: helium, neon, argon, krypton, xenon, radon. By using inert gas as protective gas, the formation of Si3N4 can be reduced.
[0067] In some embodiments, the above step (a) may include the following steps (a1) to (a3).
[0068] Step (a1) : In a reaction device, a carbon skeleton with a porous structure is heated to 400°C-550°C to remove oxygen from the carbon skeleton.
[0069] The above-mentioned reaction device is not particularly limited, and the commonly used devices in the field can be used, for example, it can be: medium frequency furnace, roller kiln, rotary kiln, push plate kiln, vertical granulation kettle, horizontal granulation kettle, vertical reactor, horizontal reactor or drum furnace and other equipment.
[0070] In step (a1), the carbon skeleton is heated to 400°C-550°C, for example, it can be heated to: 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or a value between any two values, but not limited thereto. Preferably, the carbon skeleton is heated to 450°C-550°C. By heating the carbon skeleton to the above range, the oxygen adsorbed by the carbon skeleton itself can be excluded, and the risk of the silicon deposited in the negative electrode material being oxidized by the oxygen adsorbed by the carbon skeleton itself to form high-valent silicon can be greatly reduced, so that the content of low-valent silicon in the silicon-carbon negative electrode material is maintained at a high level, which helps to reduce the content of high-valent silicon, so that C 10 , C 20 , C 30 Within the above range, a silicon-carbon negative electrode material with high lithium removal capacity is obtained.
[0071] Step (a2) : The reaction apparatus is evacuated and then an inert gas is introduced.
[0072] Through this step, the oxygen in the reaction device can be removed, which can greatly reduce the risk of silicon deposited in the negative electrode material being oxidized by the oxygen in the reaction device to form high-priced silicon, which helps to maintain the content of low-priced silicon in the silicon-carbon negative electrode material at a high level and helps to reduce the content of high-priced silicon, so that C 10 , C 20 , C 30 Within the above range.
[0073] In some embodiments, the vacuum degree in the reaction device is 1×10 -3 Pa~1×10 -6 Pa, for example, can be 1×10 -5 Pa. The smaller the pressure value in the reaction device, the less the residual amount of oxygen in the reaction device, and the lower the content of high-price silicon in the prepared silicon-carbon negative electrode material.
[0074] In some embodiments, in step (a2), after the pressure in the reaction device reaches the above pressure value and is maintained for the above time, an inert gas is introduced into the reaction device to further reduce the residual amount of oxygen in the reaction device.
[0075] In some embodiments, the above step (a2) (vacuuming, maintaining pressure, and introducing inert gas) may be repeated in a cycle. The number of times this step may be performed includes, but is not limited to: 1, 2, 3.
[0076] In some embodiments, in step (a2), the oxygen content in the tail gas discharged by the reaction device can be detected at a set frequency. When the tail gas oxygen content is less than 200ppm, step (a2) is terminated. For example, when the tail gas oxygen content is 0ppm, 20ppm, 40ppm, 60ppm, 80ppm, 100ppm, 120ppm, 140ppm, 160ppm, 180ppm, 190ppm or a range consisting of any two of these values, step (a2) can be terminated.
[0077] The order of the above steps (a1) and (a2) is not particularly limited, and step (a1) can be performed first and then step (a2), or step (a2) can be performed first and then step (a1). Through these two steps, oxygen contained in the raw materials and the reaction device is eliminated to the greatest extent.
[0078] Step (a3) : A mixed gas of silicon source gas and inert gas is introduced into the reaction device, and deposition is carried out at a temperature of 400° C. to 550° C. for 2 hours to 10 hours to form silicon-carbon particles.
[0079] The silicon source gas includes a gas that can provide silicon atoms. For example, it can be one or more of monosilane, disilane, dichlorosilane, trichlorosilane. Optionally, the silicon source gas is monosilane. The definition of the inert gas used in this step is the same as that of the inert gas in the above step (b), and argon is preferably used.
[0080] In some embodiments, a rotary kiln is used as a reaction device, and a mixed gas of monosilane and argon is introduced into the rotary kiln at a ventilation rate of 0.1L / min-4L / min, and the reaction is carried out under the conditions of a slight positive pressure of 0-0.5kPa and a rotation frequency of 0Hz-80Hz. The rotation frequency of the reaction device can be: 0Hz, 5Hz, 10Hz, 20Hz, 30Hz, 40Hz, 50Hz, 60Hz, 70Hz, 80Hz or a range consisting of any two of these values. By making the rotation frequency within the above range, the powder can be fully rotated in the kiln, the contact between the powder and the gas is strengthened, and the reaction is fully carried out.
[0081] This step (a3) is carried out after the above-mentioned steps (a1) and (a2). Since the oxygen contained in the reaction materials and the reaction device has been excluded through the above-mentioned steps (a1) and (a2), the risk of oxidation of the silicon deposited in step (a3) can be greatly reduced.
[0082] In addition, the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, the negative electrode film layer includes a negative electrode active material, and the negative electrode active material includes the silicon-carbon negative electrode material of the present application or the silicon-carbon negative electrode material prepared according to the preparation method of the present application.
[0083] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0084] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0085] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0086] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0087] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0088] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0089] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0090] In one embodiment of the present application, a secondary battery is provided.
[0091] The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack, which are described below.
[0092] Generally, a secondary battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0093] [Positive electrode]
[0094] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0095] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0096] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0097] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0098] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0099] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0100] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0101] [Electrolytes]
[0102] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0103] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0104] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0105] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0106] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0107] [Isolation film]
[0108] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0109] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0110] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0111] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0112] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0113] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0114] In some embodiments, reference Figure 2, the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0115] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0116] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0117] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0118] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0119] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0120] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0121] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0122] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0123] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0124] Example
[0125] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0126] Example 1
[0127] Preparation of silicon-carbon negative electrode materials
[0128] Step (a1): Weigh 500 g of porous carbon and place it in a rotary kiln. Heat it to 500° C. (T1) under argon protection and keep it warm for 2 hours to desorb the air adsorbed in the porous carbon.
[0129] Step (a2): Evacuate the rotary kiln to a vacuum degree of 1×10 -5 Pa, maintain the pressure for 5 minutes and then introduce argon. Repeat the steps of evacuating and introducing argon until the oxygen content in the tail gas is less than 200 ppm.
[0130] Step (a3): introducing a mixed gas of monosilane and argon (the volume ratio of monosilane to argon is 1:4) into the rotary kiln at a ventilation rate of 4 L / min, maintaining a slight positive pressure of 200 Pa, and rotating the rotary kiln at a rotation frequency of 40 Hz to obtain silicon-carbon particles.
[0131] Step (b): raising the temperature of the rotary kiln to 500°C (T2), introducing a mixed gas of acetylene, methane and argon at a pressure (P) of 0.2 kpa and a ventilation volume (V) of 3 L / min, rotating the rotary kiln at a rotation frequency of 40 Hz, and coating the above silicon-carbon particles.
[0132] Then, after natural cooling, the product was passed through a 200-mesh sieve to obtain the silicon-carbon negative electrode material.
[0133] The content of high-price silicon in silicon-carbon negative electrode materials C 10 , C 20 , C 30 Determination of.
[0134] (1) Using X-rays as an excitation source to act on the surface of the silicon-carbon negative electrode material, the area from the surface to a depth of 10 nm was detected and the Figure 7 In the XPS graph shown, the area S1 enclosed by the curve corresponding to the binding energy of 98-102eV and the baseline is the amount of low-valent silicon, and the area S2 enclosed by the curve corresponding to the binding energy of 102eV-106eV and the baseline is the amount of high-valent silicon. The content C of high-valent silicon is calculated based on S2 / (S1+S2). 10 It is 17.5%.
[0135] (2) The surface of the silicon-carbon negative electrode material (1) is etched with an argon ion gun at an etching rate of about 4 nm / min. The analysis area (i.e., the area from the surface to a depth of 10 nm) of the above (1) is etched away by adjusting the etching time to 2.5 min. Then, X-rays are used as an excitation source to act on the new surface of the silicon-carbon negative electrode material after the above etching, and the distribution information of photoelectron information is obtained at a depth of 10 nm. The silicon valence information in the area from 10 nm to 20 nm from the surface is obtained in the same manner as in (1) above. 20 It is 9.6%.
[0136] (3) The surface of the silicon-carbon negative electrode material in (2) is further etched using an argon ion gun at an etching rate of about 4 nm / min. The etching time is adjusted to 2.5 min. The analysis area in (2) is etched away, and then X-rays are used as an excitation source to act on the new surface of the etched silicon-carbon negative electrode material. The distribution information of photoelectron information is obtained at a depth of 10 nm. The silicon valence information in the area from 20 nm to 30 nm from the surface is obtained in the same manner as in (1). 30 It is 4.2%.
[0137] Preparation of secondary batteries
[0138] (a) Preparation of negative electrode sheet
[0139] The silicon-carbon composite material, conductive carbon black, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber latex (SBR) obtained above are fully stirred and mixed in a proper amount of deionized water at a weight ratio of 96.5:1.0:1.0:1.5 to form a uniform negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying and other processes, a negative electrode sheet is obtained.
[0140] (b) Preparation of positive electrode
[0141] Aluminum foil with a thickness of 8 μm was used as the positive electrode current collector. 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 93:2:5, and the positive electrode slurry is obtained after being fully stirred and mixed. Thereafter, the positive electrode slurry is evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain the positive electrode sheet.
[0142] (c) Preparation of electrolyte
[0143] The electrolyte is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, EMC and DEC is 20:20:60. Then LiPF6 is dissolved in the above organic solvent, and the additive fluoroethylene carbonate (FEC) is added, wherein the concentration of LiPF6 is 1 mol / L, and the mass proportion of FEC in the electrolyte is 5%.
[0144] (d) Preparation of batteries
[0145] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, the bare cell is welded with a pole ear, and the bare cell is placed in an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of static, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain the lithium-ion secondary battery of Example 1.
[0146] Examples 2-5 and Comparative Examples 1-2
[0147] The temperature (T2) in step (b) was changed as shown in Table 1 below. Otherwise, the silicon-carbon negative electrode material was prepared in the same manner as in Example 1. The C 10 , C 20 , C30 , and then made into a secondary battery.
[0148] For the silicon-carbon negative electrode material of Comparative Example 1, X-rays were used as an excitation source to act on the surface of the silicon-carbon negative electrode material, and the area from the surface to a depth of 10 nm was detected, and the results were obtained. Figure 8 The XPS graph shown. The high-order silicon content C 10 It is 30.3%.
[0149] The following performance tests were performed on the above embodiments and comparative examples.
[0150] <Performance Test>
[0151] (1) Lithium removal capacity and first coulombic efficiency of silicon-carbon anode materials
[0152] a. Preparation of button cell: After the above silicon-carbon negative electrode material, conductive carbon black and binder polyacrylic acid are mixed in a mass ratio of 8:1:1, deionized water is added as solvent, and the system is stirred under the action of a rapid mixer until the system is uniform to obtain a negative electrode slurry with a solid content of 45%; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil and dried at 85°C, and the electrode plate is obtained after cold pressing. Metal lithium is used as the counter electrode, Celgard 2400 isolation membrane is used, and electrolyte is injected to assemble a button cell. The electrolyte is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, EMC and DEC is 20:20:60. Then LiPF6 is dissolved in the above organic solvent, and the additive fluoroethylene carbonate (FEC) is added, wherein the concentration of LiPF6 is 1 mol / L, and the mass proportion of FEC in the electrolyte is 5%.
[0153] b. Button cell test process: After the assembled button cell has been allowed to stand for 60 minutes, it is tested by discharging at 0.05C constant current to 5mV, discharging at 50μA to 5mV, standing for 10 minutes, and charging at 0.1C to 2.0V. The lithium insertion capacity of the silicon-carbon negative electrode material is the capacity C1 when discharged to 5mV, the lithium removal capacity C2 when charged to 2.0V, and the first coulombic efficiency of the silicon-carbon negative electrode material is C2 / C1.
[0154] (2) Discharge capacity and first coulombic efficiency of secondary batteries
[0155] The secondary battery obtained by the above embodiment and comparative example was kept at a constant temperature of 25°C for 60 minutes, and then charged to 4.25V with a constant current of 0.1C, and then charged to 0.05C with a constant voltage of 4.25V, and the charged gram capacity at this time was recorded as Q1; after standing for 10 minutes, the battery was discharged to 2.5V with a constant current of 0.1C, and then discharged to 0.05C with a constant voltage of 2.5V, and the discharged gram capacity at this time was recorded as Q2, and the first coulombic efficiency of the secondary battery was Q2 / Q1.
[0156] Table 1
[0157]
[0158] Note: The volume ratio of the mixed gas in Table 1 is: the volume ratio of acetylene, methane and argon
[0159] It can be seen from the results in Table 1 that in step (b), by making the temperature, pressure, ventilation volume and mixed gas of the rotary kiln meet specific conditions, C 10 Less than 25% of silicon-carbon negative electrode material. Examples 1-5 show that by controlling the temperature of the rotary kiln at 500°C-700°C, the content of high-price silicon in the obtained silicon-carbon negative electrode material is low, and C 10 The silicon-carbon negative electrode material has high lithium removal gram capacity and first coulomb efficiency, and the obtained secondary battery has high discharge gram capacity and first coulomb efficiency. In particular, when the temperature of the rotary kiln is controlled at 550℃-650℃, the C of the obtained silicon-carbon negative electrode material is 10 further reduced to less than 20%, and C 20 and C 30 It is also further reduced, and the performance of the secondary battery is better.
[0160] Compared with Examples 1 to 5, in Comparative Examples 1 and 2, the temperature in the rotary kiln was too low (200°C) or too high (1000°C), and the C 10 If it is greater than 30%, the technical effect of the present application cannot be achieved.
[0161] Examples 6-8 and Comparative Example 3
[0162] The pressure (P) in step (b) was changed as shown in Table 2 below. Except for this, the silicon-carbon negative electrode material was prepared in the same manner as in Example 3. The C 10 , C 20 , C 30 , and then made into a secondary battery.
[0163] The performance evaluation was carried out in the same manner as in Example 3, as shown in Table 2.
[0164] Table 2
[0165]
[0166] From the results in Table 2, it can be seen that by controlling the pressure of the rotary kiln in the range of 0 kPa-1 kPa in step (b), the content of high-price silicon in the obtained silicon-carbon negative electrode material is low, and C 10 In particular, when the pressure of the rotary kiln is controlled within the range of 0 kPa-0.5 kPa, the C of the obtained silicon-carbon negative electrode material is 10 Further reduction, below 20%, and C 20 and C 30 The silicon-carbon negative electrode material has high lithium removal gram capacity and first coulomb efficiency, and the obtained secondary battery has high discharge gram capacity and first coulomb efficiency.
[0167] In Comparative Example 3, the pressure in the rotary kiln was too high (5 kpa), and the C 10 If it is greater than 25%, the technical effect of the present application cannot be achieved.
[0168] Examples 9-11 and Comparative Examples 4 and 5
[0169] The silicon-carbon negative electrode material was prepared in the same manner as in Example 3 except that the ventilation volume (V) in step (b) was changed as shown in Table 3 below, and C 10 , C 20 , C 30 , and then made into a secondary battery.
[0170] The performance evaluation was carried out in the same manner as in Example 3, as shown in Table 3.
[0171] Table 3
[0172]
[0173] From the results in Table 3, it can be seen that by controlling the ventilation volume (V) of the rotary kiln in the range of greater than 0 L / min and less than or equal to 10 L / min in step (b), the content of high-price silicon in the obtained silicon-carbon negative electrode material is low, and C 10 In Comparative Examples 4 and 5, the ventilation volume is too high or the mixed gas is not introduced, and the technical effect of the present application cannot be obtained.
[0174] Examples 12-15 and Comparative Example 6
[0175] The composition of the mixed gas in step (b) was changed as shown in Table 4 below. Except for this, the silicon-carbon negative electrode material was prepared in the same manner as in Example 3. The C 10 , C 20 , C 30 , and then made into a secondary battery.
[0176] The performance evaluation was carried out in the same manner as in Example 3, as shown in Table 4.
[0177] Table 4
[0178]
[0179] From the results in Table 4, it can be seen that in step (b), by selecting the carbon source gas from at least one of ethane, ethylene, acetylene and methane, the content of high-valent silicon in the obtained silicon-carbon negative electrode material is low, and C 10 In Comparative Example 6, a mixed gas of propane, methane and argon is used. Since the decomposition temperature of propane is too high, the uniformity and integrity of the coating are poor, resulting in an excessively high content of high-valent silicon, and the technical effect of the present application cannot be achieved.
[0180] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A silicon-carbon negative electrode material, comprising a carbon skeleton having a pore structure and a silicon-based material arranged in the pore structure, wherein in a region extending from the surface of the silicon-carbon negative electrode material to a region extending 10 nm inward from the surface, the content of the high-price silicon is less than 25% relative to the total amount of low-price silicon and high-price silicon, wherein: The low-valent silicon is silicon with a valence of 0 to 2, and the high-valent silicon is silicon with a valence of 3 to 4.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: In a region extending from the surface of the silicon-carbon negative electrode material to 10 nm inward from the surface, the content of the high-price silicon is less than or equal to 20% relative to the total amount of low-price silicon and high-price silicon.
3. The silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: In the area from 10 nm to 20 nm from the surface of the silicon-carbon negative electrode material, the content of the high-price silicon is less than or equal to 20% relative to the total amount of low-price silicon and high-price silicon, and optionally, less than or equal to 10%.
4. The silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: In the area from 20 nm to 30 nm from the surface of the silicon-carbon negative electrode material, the content of the high-price silicon is less than or equal to 10% relative to the total amount of low-price silicon and high-price silicon, and optionally, less than or equal to 5%.
5. The silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The silicon-carbon negative electrode material satisfies at least one of the following conditions: (1) The volume distribution particle size Dv50 of the silicon-carbon negative electrode material is 5 μm-10 μm, and Dv50 can be 6 μm-9 μm; (2) The specific surface area of the silicon-carbon negative electrode material is less than or equal to 5 m 2 / g, can be selected to be less than or equal to 2m 2 / g; (3) The powder compaction density of the silicon-carbon negative electrode material under a pressure of 3000N is 0.8g / cm 3 -1.2g / cm 3 , optional 0.9g / cm 3 -1.2g / cm 3 ; (4) The tap density of the silicon-carbon negative electrode material is 0.9 g / cm 3 -1.1g / cm 3 , optional 1.0g / cm 3 -1.1g / cm 3 ; (5) The lithium-free gram capacity of the silicon-carbon negative electrode material is 800mAh / g-2500mAh / g, and can be optionally 1000mAh / g-2000mAh / g.
6. The silicon-carbon negative electrode material according to any one of claims 1 to 5, characterized in that: The pore volume of the carbon skeleton is 0.4 cm 3 / g-1.5cm 3 / g, optional 0.6cm 3 / g-1.2cm 3 / g; and / or, Relative to the pore volume, the volume proportion of micropores with a pore diameter less than 2 nm is greater than or equal to 60%, and can be optionally greater than or equal to 80%.
7. The silicon-carbon negative electrode material according to any one of claims 1 to 6, characterized in that: The surface of the silicon-carbon negative electrode material has a coating layer; optionally, the coating layer is a carbon coating layer.
8. A method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 7, characterized in that: The steps include: a silicon-carbon particle forming step of reacting a carbon skeleton having a pore structure with a silicon source gas to form silicon-carbon particles having a silicon-based material in the pore structure; and The silicon-carbon particle processing step is to introduce a mixed gas including a carbon source gas and an inert gas into the silicon-carbon particles at a ventilation volume greater than 0 L / min and less than or equal to 10 L / min under the conditions of a temperature of 500°C-700°C and a pressure of 0 kpa-1 kpa, wherein the carbon source gas is selected from at least one of ethane, ethylene, acetylene, and methane.
9. The preparation method according to claim 8, characterized in that: In the silicon-carbon particle processing step, the mixed gas is introduced into the silicon-carbon particles at a flow rate of 0.5 L / min-4 L / min under the conditions of a temperature of 550° C.-650° C. and a pressure of 0 kpa-0.5 kpa.
10. The preparation method according to claim 8 or 9, characterized in that: The mixed gas comprises 10% to 70% by volume of acetylene, 0% to 20% by volume of methane and 10% to 90% by volume of an inert gas; Optionally, the mixed gas includes 15% to 60% by volume of acetylene, 5% to 10% by volume of methane and 30% to 80% by volume of inert gas.
11. The preparation method according to any one of claims 8 to 10, characterized in that: The step of forming silicon-carbon particles includes the following steps: The reaction apparatus was evacuated and then an inert gas was introduced.
12. The preparation method according to any one of claims 8 to 11, characterized in that: The step of forming silicon-carbon particles includes the following steps: In a reaction device, a carbon skeleton with a porous structure is heated to 400° C.-550° C. to remove oxygen from the carbon skeleton.
13. The preparation method according to any one of claims 8 to 12, characterized in that: The step of forming silicon-carbon particles includes the following steps: A mixed gas of silicon source gas and inert gas is introduced into the reaction device, and deposition is performed at a temperature of 400° C. to 550° C. for 2 to 10 hours to form silicon-carbon particles.
14. The preparation method according to any one of claims 8 to 13, characterized in that: The silicon source gas is selected from one or more of monosilane, disilane, dichlorosilane, and trichlorosilane. Optionally, the silicon source gas is monosilane.
15. The preparation method according to any one of claims 8 to 14, characterized in that: The inert gas is argon.
16. A negative electrode plate, characterized in that: The invention comprises the silicon-carbon negative electrode material according to any one of claims 1 to 7 or the silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 8 to 15.
17. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 16.
18. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 17.
Citation Information
Patent Citations
Negative electrode active material, negative electrode, lithium-ion secondary battery, method for using lithium-ion secondary battery, method for producing negative electrode active material, and method for producing lithium-ion secondary battery
CN109155406A
Lithium ion battery silicon-carbon composite anode material, preparation method and application thereof
CN109713259A
Silicon carbon anode material and preparation method thereof
CN110416500A
Carbon-coated silicon monoxide negative electrode material, preparation method thereof and lithium ion battery
CN114464785A
Anode material of secondary battery and manufacturing method the same
KR1020160054932A